The study of catalyc activity of iron bispidon complex in air drying alkyd - Křižan, Martin; Erben, Milan; Kalenda, Petr; Honzíček, Jan; Vinklárek, Jaromír (Česká společnost průmyslové chemie, 2016)
Oxidizing alkyds are polymeric binders, which are prepared from polyols, dicarboxylic acids and fatty acid. Alkyds are one of the most widespread used binders in coating industry. The curing process of alkyd is usually called autoxidation. Presented work is focused on elucidation of the mechanism of catalytic behavior of iron bispidon complex in the autoxidation process. We have prepared new iron-based drier containing diazabicyclo[3.3.1]nonan-9-one (bispidon) ligand in the molecule. Autoxidation activity of prepared compounds was examined on both ethyl linoleate and commercially available alkyd. The autoxidation process was followed by time-dependent IR spectroscopy. On analysis of obtained data, the activity of selected driers has been determined and particular reactions involved in autoxidation were resolved.
Studium katalytické aktivity bispidonového komplexu železa v alkydu
Keywords: alkyd; iron; bispidone; alkyd; železo; bispidon